Prevalence of latent tuberculosis infection among participants of the national LTBI screening program in South Korea – A problem of low coverage rate with current LTBI strategy - Kim, Hyung Woo; Min, Jinsoo; Choi, Joon Young; Shin, Ah Young; Myong, Jun-Pyo; Lee, Yunhee; Yim, Hyeon Woo; Jeong, Hyunsuk; Bae, Sanghyuk; Choi, Hoyong; In, Hyekyung; Park, Ahyoung; et al. (Frontiers in Public Health, 2023)
Background The Government of South Korea launched a national preemptive latent tuberculosis infection (LTBI) screening program in 2016, including more than 1. 6 million population in congregate settings. The objective of this study was to analyze LTBI prevalence and its risk factors in each setting. Additionally, the proportion of LTBI pool covered by the current national LTBI strategy was investigated. Methods Database for results of interferon gamma release assay (IGRA), X-ray, and baseline demographic information was linked with National Health Information Database, national tuberculosis (TB) surveillance database, and national contact investigation database. Participants were categorized into three groups: Group A, workers of postpartum care centers, social welfare facilities and educational institutions; Group B, first year students in high school and out-of-school youths; and Group C, inmates of correctional facilities. Relative risks of LTBI by sex, age, place of living, income level, and comorbidities were calculated. Results A total of 444,394 participants in Group A, 272,224 participants in Group B, and 11,511 participants in Group C who participated in the national LTBI screening program between 2017 and 2018 were included, with LTBI prevalence of 20.7, 2.0, and 33.2%, respectively. Age was the single most important risk factor in Group A and Group C. Low-income level was another risk factor commonly identified in all groups. Among participants with positive IGRA results, 2.7, 4.4, and 3.3% in Groups A, B and C, respectively, had past TB exposure history since 2013. Current LTBI guideline targeting high or moderate TB risk disease covered 6.5, 0.6, and 1.1% of participants with positive IGRA results in Groups A, B and C, respectively. Conclusion Only a small proportion of participants with positive IGRA results could be covered by the current LTBI strategy. Expansion of LTBI strategy by identifying further high-TB risk group in the general population is required.